The development of egalitarianism, altruism, spite and parochialism in childhood and adolescence - Ernst Fehr; Daniela Rützler; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study how the distribution of other-regarding preferences develops with age. Based on a set of allocation choices, we can classify each of 717 subjects, aged 8 to 17 years, as either egalitarian, altruistic, or spiteful. Varying the allocation recipient as either an in-group or an out-group member, we can also study how parochialism develops with age. We find a strong decrease in spitefulness with increasing age. Egalitarianism becomes less frequent, and altruism much more prominent, with age. Women are more frequently classified as egalitarian than men, and less often as altruistic. Parochialism first becomes significant in the teenage years.
Keywords: C91; D03; 330; other-regarding preferences; egalitarianism; altruism; spite; parochialism; experiments with children and adolescents; Soziale Beziehungen; Präferenztheorie; Kinder; Lebensverlauf; Test; Gerechtigkeit; Altruismus